Service Quality, Customer Relationship Management, and Brand Image On Consumer Decisions (Expedition Services In Solo City) - Romadhoni Khoiruddin; Nasir, Moechammad (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2024)
This study is intended to analyze the impact of service quality, customer relationship management, and brand image on consumer decisions regarding the use of expedition services in Solo City. This study uses an explanatory research type with a quantitative method measured using a Likert scale. The data analysis in this research utilizes SPSS version 23. The sample for this research refers to the calculation by Hair et al. (2010), which involves multiplying the total number of indicators in this study by a range of 5 to 10. This study uses 17 question indicators, resulting in a calculation of 17 multiplied by 6, which equals 102. Therefore, a sample of 102 respondents was used. The data collection technique employed was distributing questionnaires via Google Forms. Additionally, the collected respondent data will be classified according to gender, age, education, occupation, and income level. The research results indicate that the variables of service quality, customer relationship management, and brand image have a positive and significant impact on the decision to use expedition services in Solo City.